Evaluation of seroprevalence of and risk factors for bruceliosis in aborted sheep herds in the province konya - Zeki Aras; Mehmet Ateş (Eurasian Journal of Veterinary Sciences)
Brusellosis, is a zoonotic infection and cause reproductive system disorders such as abortion and infertility in animals. A number of 588 blood serum samples collected from 24 herds were examined by RBPT, mSAT and ELlSA tests to determine the frequency of the disease in the B. melitensis (B. melitensis) isolation positive sheep herds from province Konya. Besides, a structured questionnaire was used to collect information on the sheep herds' health and management to evaluate risk factors of sheep herds. Of the 588 serum samples, 242 (41.1%), 219 (37.2%) and 254 (43.2%) were found to be positive by RBPT, mSAT and ELISA, respectively . Epidemiological information of herds was determinated by questionnaire. It is concluded from this study that the B. melitensis isolation positive herds have a lot of sero-positive animals found between 24-81.8% depending on the herd tested and such sero-positivity is concern of public health and animal husbandry.